Pengarusutamaan Gender Di Kantor Pelayanan Pajak Pratama Tanjung Karang - Putri Rahayu; Eko Budi Sulistio (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2019)
Gender issues have now become regional commitment, nationally, and internationally. Presidential Instruction No. 9 of 2000 on gender mainstreaming, pressed the importance of mainstreaming gender in order to realize a good governance.Employees are an important asset at any Tax Services Office, due to the growing development of the agencies depend on the performance of its officers. Directorate General of Taxes as one of the organizations under the auspices of the Ministry of Finance also participate in this support PUG, namely by applying the concept of Gender Responsive. This concept is also applied throughout the organization under the auspices of the Directorate General of taxation including Tax Services Office Pratama Tanjung Karang. In this study the researchers wanted to know what are the programs, how the implementation and what are the factors supporting and restricting in Mainstreaming Gender in the KPP Pratama Tanjung Karang. The theory used in this study is gender theory and the theory of Justice. This research is a descriptive research with qualitative approach by taking data from 22 informant through interviews, observation and the documentation. From this research it is achieved that mainstreaming gender in KPP Pratama Tanjung Karang already can be seen from the aspects of political support, policy, institutional, information systems and human resources. But there are some things that should be fixed, namely toilet for taxpayers as well as a smoking area and a woman parking should be eliminated.